Green Skills and Labor Market Transformation: A Bibliometric Analysis of Global Research Trends - Duygu Celayir (European Scientific Journal, ESJ, 2026)
The rapid transition towards a green economy has led to heightened attention on the acquisition of green skills and sustainable education structures responsive to expanding labour market demands. At this point, the interlinkages among environmental literacy, vocational training, and employability have formed the focal point of global policy and research debates. This study offers a bibliometric mapping of global scholastic literature on green skills and labour market change. On the basis of data extracted from the Web of Science Core Collection and run through bibliometric mapping tools, this study captures the intellectual terrain, top researchers, thematic clusters, and time trends characterising this topic.The review detects an increasingly expanding body of literature with significant contributions from interdisciplinary areas, particularly environmental sciences, education, and labour economics. Emerging themes are such as just transition policies, green sector skill mismatch, and mainstreaming sustainability competence in formal and vocational schooling. Co-authorship networks and collaboration patterns at the country level also support the global nature of the debate. This study offers valuable guidance for policymakers, educators, and researchers focused on connecting workforce development policy to the demands of economic and ecological sustainability.